A Guide in the Process of Cognitive Behavioral Therapy in Obsessive Compulsive Disorder: Formulation - Nergis LAPSEKİLİ; Mehmet AK (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Introduction: The implementation of effective treatment depends on thorough understanding of disorder and its presentation. Treatment strategies must depend on the individual formulation of the patient. In this paper an Obsessive Compulsive Disorder(OCD) patient treated with Cognitive Behavioral Therapy (CBT) methods is presented. It is discussed that in the therapy, formulation is an ongoing dynamic process and necessarily required for the effectiveness of therapy. Case: Y.B. was 32 years old, single male patient graduated from university. He applied because of his obsessions and compulsions. He was diagnosed OCD after the psychiatric evaluation according to Diagnostic and Statistical Manual of Mental Disorders-IV(DSM-IV). In treatment following strategies were applied: 1) Cognitive restructuring of the thoughtaction- fusion, anxiety intolerance, overestimated threat appraisals, 2) exposure and response prevention techniques aimed to test if catastrophic expectations would occur. Discussion: When planning CBT for the treatment of OCD, the first and most important step is a good formulation created with the data obtained from a good evaluation process. Treatment planning in our case was planned on using cognitive restructing techniques for thought-action-fusion, anxiety intolerance and overestimated threat appraisals but the formulation was completed in the course of treatment when the patient could talk about his early experiences. As a result, the formulation is a roadmap that should be taken into consideration at every stage of therapy. Its presence is essential to reach the correct destination and it is a dynamic process needed to be updated according to the information from the patient